Mechanism of Colloidal Attachment on Textile Fibrous Media - Sukumar Roy; Subrata Ghosh; Niranjan Bhowmick (Tekstilec, 2019)
Filtration through the porous media of a granular bed is one of the oldest and most favourable particle separation techniques used universally for the treatment of water. In the case of filtration through a granular bed, all physical factors are incorporated into a single collector contact efficiency. The latter is the ratio of the rate at which particles strike the collector to the rate at which particles flow towards the collector. On the other hand, collision or attachment efficiency represents the chemical interaction between the media used and colloids, and is expressed as the ratio of the number of particles removed by the collector to the number of particle collector collisions, or the possibility that a collision in an attachment. Textile media is emerging as a substrate in deep bed filtration due to its superior performance in the removal of colloidal particles from water under higher filtration velocities compared with granular media. Reported studies relating to the effect of physicochemical factors on colloidal removal in textile fibrous media are mainly based on the experimental value of the concentration variation of colloidal particles in input and output water. Presented in this paper is a way in which colloidal filtration theory can be extended to textile filter media in order to explain the mechanism of attachment of colloids (primarily bacteria) on a textile fibrous media surface.